Living standards, poverty and inequality in the UK: 2016-2017 to 2021-2022 - Andrew Hood; Tom Waters (Institute for Fiscal Studies (IFS), 2017)
Debates over living standards, poverty and inequality in the UK are often hampered by the fact that official data on household incomes are available only with a significant lag. Currently, the latest statistics are for 2014-15. In this report, we attempt to fill this gap by estimating what has happened to household incomes between 2014-15 and 2016-17 based on other data sources and changes to direct tax and benefit policy. We then estimate how the incomes of different households would evolve up to 2021-22 if current tax and benefit policy plans are kept to and if the macroeconomic forecasts from the Office for Budget Responsibility (OBR) - for things such as earnings and employment - were correct. We also consider macroeconomic scenarios that are more and less optimistic than the OBR's central forecast.
Keywords: 330